Association of organs-crosstalk with the pathogenesis of osteoarthritis: cartilage as a key player - Yingda Qin; Jingkai Di; Zijian Guo; Shuai Chen; Chuan Xiang (Frontiers in Endocrinology)
Degeneration of articular cartilage is the hallmark pathologic change in osteoarthritis (OA). Cartilage not only serves as a shock-absorbing structure for movement but is also regulated by organs other than bone, while chondrocytes secrete cytokines that influence these organs. The concept of organ axis refers to the regulatory pathways formed between organs via cytokine signaling. The communication network established between cartilage and other organs constitutes the cartilage-organ axis. Through this axis, these organs regulate articular chondrocyte proliferation and apoptosis. It is evident that chondrocytes play a central role in connecting various organs to the progression of OA, prompting interest in strategies to intervene in cartilage damage by modulating the organ axis. This review presents, for the first time, a system summarizing the effects of the extraosseous system on cartilage through various factors that alter OA progression. The aim is to fully elucidate the effects of different organs on cartilage, thus providing insights into the treatment of OA and systemic diseases.